PERNIKAHAN WANITA HAMIL DIBAWAH UMUR DALAM PERSPEKTIF HUKUM ISLAM DI KUA PASARKLIWON TAHUN 2022-2023 - Fahryan, Dhafi; Syamsuddin, S; Baehaqi, B (AL HUKMU: Journal of Islamic Law and Economics, 2023)
Marriage is a physical and mental bond between a man and a woman as husband and wife, with the aim of forming a happy and eternal family (household) based on God Almighty. Meanwhile, according to Dadang Hawari, marriage is a bond between a man and a woman as husband and wife based on the law (Law), religious law or applicable customs (Hawari, 2006: 58). However, in social life we often find marriages that are carried out due to certain circumstances, one of which is the marriage of a pregnant woman and underage or underage marriage. This problem occurs a lot in modern times like today because of promiscuity and lack of parental supervision of children. In fact, if we look at the legal point of view of the issue of marriage for women who are pregnant, according to the scholars, there are those who allow it and some do not allow it. According to the majority of scholars, the law of marrying a minor is permissible. In fact, it has been agreed by all scholars said by a scholar that it is permissible to marry a minor. This research takes a case in the area in the KUA of Pasarkliwon District, Surakarta City which occurred in the period 2022-2023. This study aims to analyze the review of Islamic law and the applicable law in Indonesia on the marriage of pregnant women underage and analyze the positive impact and negative impact of Marriage of Pregnant Women underage. This research uses a qualitative descriptive method, namely research that seeks to tell the solution of existing problems now based on data. The results showed that according to Islamic law, the marriage of underage pregnant women and the marriage of underage women in the perspective of Islamic law is permissible, taking into account the benefits for the couple in the future and the implementation of marriage of pregnant or underage women in the KUA Pasar Kliwon District of Surakarta City, has fulfilled the rules set by the Government of the Unitary State of the Republic of Indonesia, in this case the Ministry of Religion of the Republic of Indonesia.